2019
DOI: 10.1136/annrheumdis-2019-216303
|View full text |Cite
|
Sign up to set email alerts
|

Withdrawal of low-dose prednisone in SLE patients with a clinically quiescent disease for more than 1 year: a randomised clinical trial

Abstract: ObjectivesTo compare the efficacy to prevent flares of maintenance versus withdrawal of 5 mg/day prednisone in systemic lupus erythematosus (SLE) patients with clinically quiescent disease.MethodsA monocentric, 12-month, superiority, open-label, randomised (1:1) controlled trial was conducted with 61 patients continuing 5 mg/day prednisone and 63 stopping it. Eligibility criteria were SLE patients who, during the year preceding the inclusion, had a clinically inactive disease and a stable SLE treatment includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
74
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 109 publications
(80 citation statements)
references
References 42 publications
1
74
1
4
Order By: Relevance
“…After prednisone withdrawal, the 12-month flare incidence increased from 7% to 27%. 12 In other words, pursuing higher treatment goals such as glucocorticoid-free Doris remission 11 in patients with an established low disease activity may subject them to flare risks. Whether metformin add-on could facilitate achieving these higher treatment goals in low-activity patients with SLE by preventing flares is yet to be explored.…”
Section: Discussionmentioning
confidence: 99%
“…After prednisone withdrawal, the 12-month flare incidence increased from 7% to 27%. 12 In other words, pursuing higher treatment goals such as glucocorticoid-free Doris remission 11 in patients with an established low disease activity may subject them to flare risks. Whether metformin add-on could facilitate achieving these higher treatment goals in low-activity patients with SLE by preventing flares is yet to be explored.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective study by Tani et al suggests that the time interval from the last flare to the steroid withdrawal may also play a role in future flares 5. Interestingly, the quiescent time was more in the withdrawal group in CORTICOLUP study, although not significant 1…”
mentioning
confidence: 87%
“…The above-mentioned study by Mathian et al (CORTICOLUP study) provides scientific evidence addressing this issue. The study has successfully shown the superiority of glucocorticoid maintenance therapy over its withdrawal both in terms of all flares and severe flares 1. The follow-up period was only 52 weeks, yet the number of flares in the withdrawal group were quite high (27% vs 7%) with a HR of 0.2.…”
mentioning
confidence: 92%
“…Response to: 'Comments on the article: "Withdrawal of low-dose prednisone in SLE patients with a clinically quiescent disease for more than 1 year: a randomised clinical trial"' by Mousavi and Taherifard We thank Mousavi et al for their interest in our study. 1 2 Mousavi et al regret that we did not take into account different factors determined in the literature to be associated with increased risk of flare of the disease, such as 'African American ethnicity', disease onset ≤25 years and B Lymphocyte Stimulator (BLyS) serum levels ≥2 ng/mL. 3 4 ), while in the CORTICOLUP study only clinically quiescent patients were included.…”
mentioning
confidence: 99%